Inertial Algorithms for Bifunction Harmonic Variational Inequalities - AlShejari, A. A.; Noor, M. A.; Noor, K. I. (International journal of analysis and applications, 2024)
In this paper, we introduce and study some new classes of bifunction harmonic variational inequalities. Various new and known classes of variational inequalities and complementarity problems can obtained as special classes of bifunction harmonic variational inequalities. The auxiliary principle technique is applied to suggest and analyze some hybrid inertial iterative methods for finding the approximate solutions of the bifunction harmonic variational inequalities. The convergence analysis of these iterative methods is also considered under some suitable conditions. Results proved in this paper can be viewed as a refinement and improvement of the known results. It is an interesting open problem to develop some implementable numerical methods for solving these problems and to explore the applications in mathematical and engineering sciences.